Expression of AgNOR in histopathologically diagnosed gastric carcinoma patients - Flora, Thanadar Ajmiree; Kabir, Enamul; Begum, Shahnaj; Khan, Rizwana Rahman; Gaffar, Tania; Tapu, Thanadar Tamjeeda (International Journal of Research in Medical Sciences, 2021)
Background: Worldwide, gastric cancer is the second leading cause of cancer-related fatalities, after lung cancer. Identifying stomach cancer without relying entirely on histopathology is critical. The Silver-stained nucleolar organizer regions (AgNOR’s) reflect the aggressiveness of the tumor, according to the study. To establish the effectiveness of these approaches in detecting stomach cancer, the present study was done in order to test their efficacy. The aim of the study was to observe expression of AgNOR in histopathologically diagnosed gastric carcinoma patients. Methods: This cross-sectional analytical study was carried out in the department of pathology, Sir Salimullah Medical College, Dhaka, Bangladesh from July 2017 to June 2019. A total of 60 adults who were histopathologically diagnosed patients with gastric carcinoma in gastric endoscopic biopsies and resected samples. Results: More than one-third of the patients (38.3%) belonged to the age group of 61-70 years. The age range of the participants was 40-82. 55% were male and 45% were female, 63.3% of the cancers were in the pylorus region, 33.3% were in the body and 3.3% were in the cardiac end. 80% of the GC were intestinal type and 20% were of diffuse type. 50% of the cancers were moderately differentiated, 36.67% were poorly differentiated, and 13.33% were well differentiated. The association between histopathological grading of gastric carcinoma and AgNOR was statistically significant. Conclusions: The growth of the tumor is highly variable. The AgNOR stain is also a good marker to detect the proliferation of tumor cells.